2019
DOI: 10.3389/fphar.2019.00018
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Blockade of Soluble Epoxide Hydrolase Attenuates the Progression of Congestive Heart Failure Combined With Chronic Kidney Disease: Insights From Studies With Fawn-Hooded Hypertensive Rats

Abstract: An association between congestive heart failure (CHF) and chronic kidney disease (CKD) results in extremely poor patient survival rates. Previous studies have shown that increasing kidney epoxyeicosatrienoic acids (EETs) by blocking soluble epoxide hydrolase (sEH), an enzyme responsible for EETs degradation, improves the survival rate in CHF induced by aorto-caval fistula (ACF) and attenuates CKD progression. This prompted us to examine if sEH inhibitor treatment would improve the outcome if both experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 51 publications
(107 reference statements)
2
13
0
Order By: Relevance
“…Second, our hypothesis was that potential beneficial effects of RDN on the course of CHF in ACF TGR are dominantly mediated by improvement of renal function. We showed previously that RBF is decreased at the very early stage of compensation phase of ACF-induced CHF, and persistent renal dysfunction rather than progressing cardiac remodeling was responsible for the reduction in long-term survival rate [12, 13, 31, 44]. In addition, our recent study has suggested that altered renal vascular responsiveness, particularly exaggerated renal vascular responsiveness, to ANG II might play an important role in the development of renal dysfunction and can accelerate the decompensation of CHF in ACF TGR [14].…”
Section: Discussionmentioning
confidence: 99%
“…Second, our hypothesis was that potential beneficial effects of RDN on the course of CHF in ACF TGR are dominantly mediated by improvement of renal function. We showed previously that RBF is decreased at the very early stage of compensation phase of ACF-induced CHF, and persistent renal dysfunction rather than progressing cardiac remodeling was responsible for the reduction in long-term survival rate [12, 13, 31, 44]. In addition, our recent study has suggested that altered renal vascular responsiveness, particularly exaggerated renal vascular responsiveness, to ANG II might play an important role in the development of renal dysfunction and can accelerate the decompensation of CHF in ACF TGR [14].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of EETs in ACF-induced volume overload-related cardiac remodeling have been studied previously ( Cervenka et al, 2015a , b ; Sporkova et al, 2017 ; Kala et al, 2018 ; Vackova et al, 2019a , b ). It is demonstrated that the level of EETs is downregulated in the heart of ACF animals, while the expression of sEH is upregulated ( Cervenka et al, 2015a , b ).…”
Section: The Role Of Eets In Different Models Of Cardiac Remodelingmentioning
confidence: 99%
“…On the other hand, another sEH inhibitor GSK2256294 did not reverse LV dysfunction induced by pressure overload in both mice and rats, in spite of the fact that the increased an EETs-to-DHETs ratio was observed (Morgan et al, 2013). Similarly, c -AUCB did not alter LV contractility in hypertensive TGR and Fawn-hooded rats as well as normotensive HanSD and Fawn-hooded low-pressure rats subjected to volume overload (Červenka et al, 2015a,b; Vacková et al, 2019).…”
Section: Discussionmentioning
confidence: 84%